2009
DOI: 10.2298/aci0902061s
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between femur's length and morphometric parameters of distal femur important in rupture anterior cruciate ligament

Abstract: Femur's length increasing also produces increasing of absolute anatomical parametars of distal femur which can produce rupture of anterior cruciate ligament, while relative dimensions do not show femur's length increasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…This is in accordance However in both the ACL-injured and ACL-intact groups, there was no statistical significant differences in NWI, M:L Ratio, ACL angle of inclination between the men and women. Our results are in contrast to the findings by Shelbourne KD and Stijak L [8,9]. Vrooijink et al [16] showed that significant differences were found for bicondylar width (p=0.001), medial condylar width (p=0.002), and lateral condyle width (p=0.002) between male and female subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in accordance However in both the ACL-injured and ACL-intact groups, there was no statistical significant differences in NWI, M:L Ratio, ACL angle of inclination between the men and women. Our results are in contrast to the findings by Shelbourne KD and Stijak L [8,9]. Vrooijink et al [16] showed that significant differences were found for bicondylar width (p=0.001), medial condylar width (p=0.002), and lateral condyle width (p=0.002) between male and female subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…The breadth of the lateral femoral condyle at the level of the popliteal notch amounts to 27 mm, and at the level of the lateral epicondyle, it is 33.5 mm [14]. These results, obtained by direct measurement on macerated thigh bones speak in favour of the fact that by drilling the femoral tunnel perpendicularly to the medial aspect of the lateral condyle, a length of the tunnel which is somewhat greater than the breadth of the condyle at the level of the popliteal notch can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The breadth of the lateral femoral condyle at the level of the popliteal notch amounts to 27 mm, and at the level of the lateral epicondyle to 33.5 mm 10 . These results, obtained by a direct measurement on macerated thigh bones speak in favor of the fact that, by drilling the femoral tunnel perpendicularly to the medial aspect of the lateral condyle, a length of the tunnel which is rather greater than the breadth of the condyle at the level of the popliteal notch, can be achieved.…”
Section: Discussionmentioning
confidence: 99%